4 - Mécanismes financiers de la coopération arabo-africaine - Charbel ZAROUR, (Africa Development, 1986)
Following the 1973-74 oil crisis, Arab petroleum exporting countries appeared as major aid donors and sought to strengthen their co-operation links with Third World countries in general and African countries particularly. Arab aid took mostly the form of funds and in an effort to institutionalize such a co-operation Arab countries developed specific systems of temporary resources transfer by setting up bilateral and multilateral development Funds and Banks. These institutions were established in response to Arab countries' willingness to help Third World and African non-Arab countries. This is how BADEA, FASAA and F AT A A came to be. These institutions fund other areas than projects of course, however the bulk of their activity is geared toward project aid. In the paper the specific features of these development banks and funds are reviewed, the date on which they were established are given and for each Fund the author puts forth the available resources (including capital and reserve fund), areas of action, types and terms of aid, the volume of aid granted per country and per sector as well as trends in non-Arab African countries. Finally the relationships between Arab development Funds and banks and Western donors are developed at length. This analysis is in fact meant to try and unveil the actual nature of the relationships existing between Arab Funds and Western institutions, behind adopted strategies. These relationships will be examined from the perspective of North South strifing relationships or from that of an extension of North-South relationships.